1975
DOI: 10.1128/jcm.1.3.302-308.1975
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory experience with a radiometric method for detecting bacteremia

Abstract: Two bacteriologic systems for detecting bacteria in blood were compared; the automated radiometric BACTEC and the conventional method used in our laboratory for many years. BACTEC consisted of two bottles with 30 ml and the conventional method with 50 ml of media for aerobes and anaerobes. The BACTEC bottles were inoculated with 2 to 3 ml and the conventional with 4 to 5 ml of blood at the patient's bedside. Out of the 3,045 blood specimens cultured (804 patients), 262 (117 patients) were positive by one or bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…In this controlled evaluation, the Bactec two-bottle set recovered 11% more bacteria and fungi and did so faster in 18% of samples than a single bottle of SPB with equal volumes of blood in both. This result confirms the early results obtained with the Bactec system (2,5,15,18,22,25). However, one might have expected that acridine orange staining would have matched the speed of radiometric detection, since other studies have shown the utility of early acridine orange screening in the rapid detection of bacteremia (9, 10,12,14,23).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In this controlled evaluation, the Bactec two-bottle set recovered 11% more bacteria and fungi and did so faster in 18% of samples than a single bottle of SPB with equal volumes of blood in both. This result confirms the early results obtained with the Bactec system (2,5,15,18,22,25). However, one might have expected that acridine orange staining would have matched the speed of radiometric detection, since other studies have shown the utility of early acridine orange screening in the rapid detection of bacteremia (9, 10,12,14,23).…”
Section: Discussionsupporting
confidence: 84%
“…Few clinical studies have been done to compare Bactec with a conventional broth culture method; none has been published since 1975, although both aerobic and anaerobic Bactec media have been modified since then. In early trials, Bactec detected positive cultures earlier, and had a yield similar to conventional broth cultures (2,5,15,17,22,24), but the volume of blood cultured in these studies was usually not the same; early Gram stains and subcultures of conventional bottles were not performed, so that slower recovery in the conventional system was predictable. Moreover, these studies were done before acridine orange staining had been recognized as a useful early screening method (12,14,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recovery rate in the radiometric system in this study was higher than previously reported. A few investigators reported a recovery rate of about 90% (5,28), but generally a recovery rate of about 80% was demonstrated (8, 23, 25, 31).…”
Section: Discussionmentioning
confidence: 99%
“…Since DeLand & Wagner (9) in 1969 first described a radiometric method for detection of bacteria in blood, several investigators have reported promising results with the radiometric system, BactecB. This system has been shown to be faster than some of the conventional methods used today and comparable with respect to the detection rate (5, 8, 9, 10, 23, 28, 31).…”
mentioning
confidence: 99%